Adherence to a shoulder dysfunction physical therapy protocol after neck dissection with accessory nerve preservation in head-and-neck cancer patients: An uncontrolled clinical tria - Mozzini, Carolina Barreto; Rodrigues, Telma Ribeiro; Bergmann, Anke; Roussenq, Suellen Cristina; Kowalski, Luis Paulo; Carvalho, André Lopes (International Journal of Health Sciences, 2022)
Objective: Accessory nerve (AN) manipulation or resection during neck dissection (ND) generates accessory nerve shoulder dysfunction (ANSD). The aim of the present study was to assess adherence to a supervised physiotherapy protocol and subsequent changes in the functionality scores of patients with ASND with accessory nerve (AN) preservation. Methods: This study consisted of an uncontrolled clinical trial was carried out at the Department of Head and Neck Surgery and Otorhinolaryngology at the A.C. Camargo Cancer Center, comprising progressive isotonic and isometric strengthening of scapular stabilizer muscles. In patients with head-and-neck cancer underwent ND with AN preservation and patients with ANSD. Shoulder range of motion (ROM), middle trapezius, lower trapezius, rhomboid and anterior serratus muscle strength, pain, and quality of life (QoL) were measured in the pre-operative and 1st and 3rd post-operative months. There were included patients over 18 years old, with head-and-neck cancer who underwent ND with AN preservation and patients with ANSD. Results: A total of 55 patients were evaluated, with a mean age of 53 (±13.23). Significant improvement in the functionality scores of almost all variables between pre- and post- physiotherapy was observed. Most patients (70.9%) adhered and completed the protocol, obtaining significantly greater ROM abduction (P = 0.009) and lower trapezius strength (P = 0.011) than partially performing patients. Conclusion: When performed completely, the proposed physiotherapy protocol can minimize loss in muscle movements and strength, especially limited after ND. The results indicate that the proposed protocol is safe and has the potential to reduce ANSD.